Susceptibility to Tuberculosis Is Associated With PI3K-Dependent Increased Mobilization of Neutrophils - Leisching, Gina R. (Frontiers in Immunology, 2018)
Neutrophilia is a condition commonly observed in patients with late-stage tuberculosis, but evidence suggests that increased neutrophil influx begins early after infection in susceptible hosts and functions to promote a nutrient-replete niche that promotes M.tb survival and persistence. As the disease progresses, an increase in the number of neutrophil-like cells is observed, all of which exhibit characteristics associated with i) phenotypic and biochemical features of immaturity, ii) the inability to activate T-cells, iii) hyper-inflammation, and iv) prolonged survival. Transcriptomics reveal a common set of molecules associated with the PI3-Kinase pathway that are dysregulated in patients with active TB. Closer inspection of their individual biological roles reveal their ability to modulate the IL-17/G-CSF axis, induce leukocyte receptor activation and regulate apoptosis and motility. This review draws attention to neutrophil hyper-reactivity as a driving force for both the establishment and progression of tuberculosis disease in susceptible individuals.